2016
DOI: 10.3897/zookeys.610.8507
|View full text |Cite
|
Sign up to set email alerts
|

A new species of frog of the genus Pristimantis from Tingo María National Park, Huánuco Department, central Peru (Anura, Craugastoridae)

Abstract: A new species of Craugastoridae frog encountered from 1000–1700 m in elevation in the premontane forests of the Peruvian central Andes is described. The new species is similar in appearance to many other species of Pristimantis, but is easily distinguishable from these species by having bright red coloration on the groin, posterior surface of thighs, and shanks. The new species is only known for two localities 27 km apart in the Huánuco Region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…Sequences from Diasporus , Eleutherodactylus , Holoaden , Hypodactylus, Ischnocnema , Lynchius , Oreobates , and Strabomantis were also used as external groups. GenBank sequences employed correspond to data previously reported by Darst and Cannatella (2004) , Faivovich et al (2005) , Elmer et al (2007) , Heinicke et al (2007 , 2009 , 2015 ), Hedges et al (2008) , Arteaga-Navarro and Guayasamin (2011) , Fouquet et al (2012) , Kok et al (2012 , 2018 ), Lehr et al (2012 , 2017 ), Lehr and Von May (2017) , Pinto-Sánchez et al (2012) , Arteaga et al (2013 , 2016 ), Barrio-Amorós et al (2013) , Crawford et al (2013) , Zhang et al (2013) , Ortega-Andrade and Venegas (2014) , Rivera-Prieto et al (2014) , Hutter and Guayasamin (2015) , Rivera-Correa and Daza (2015) , Chávez and Catenazzi (2016) , de Oliveira et al (2017) , García-R. et al (2012) , Shepack et al (2016) , Székely et al (2016) , González-Durán et al (2017) , Guayasamin et al 2015 , Guayasamin et al 2017 , Jablonski et al (2017) , von May et al (2017) , Mahecha et al (unpub.).…”
Section: Methodsmentioning
confidence: 78%
“…Sequences from Diasporus , Eleutherodactylus , Holoaden , Hypodactylus, Ischnocnema , Lynchius , Oreobates , and Strabomantis were also used as external groups. GenBank sequences employed correspond to data previously reported by Darst and Cannatella (2004) , Faivovich et al (2005) , Elmer et al (2007) , Heinicke et al (2007 , 2009 , 2015 ), Hedges et al (2008) , Arteaga-Navarro and Guayasamin (2011) , Fouquet et al (2012) , Kok et al (2012 , 2018 ), Lehr et al (2012 , 2017 ), Lehr and Von May (2017) , Pinto-Sánchez et al (2012) , Arteaga et al (2013 , 2016 ), Barrio-Amorós et al (2013) , Crawford et al (2013) , Zhang et al (2013) , Ortega-Andrade and Venegas (2014) , Rivera-Prieto et al (2014) , Hutter and Guayasamin (2015) , Rivera-Correa and Daza (2015) , Chávez and Catenazzi (2016) , de Oliveira et al (2017) , García-R. et al (2012) , Shepack et al (2016) , Székely et al (2016) , González-Durán et al (2017) , Guayasamin et al 2015 , Guayasamin et al 2017 , Jablonski et al (2017) , von May et al (2017) , Mahecha et al (unpub.).…”
Section: Methodsmentioning
confidence: 78%
“…Therefore, we included sequences used in previous studies on P. lacrimosus group (e.g. Arteaga et al 2013;Padial et al 2014;Ortega-Andrade et al 2015;Rivera-Correa and Daza 2016;Chávez and Catenazzi 2016;Shepack et al 2016;Guayasamin et al 2017;Ron et al 2020;Rivera-Correa and Daza 2020). Samples of Niceforonia nigrovittata (Andersson, 1945), N. elassodisca (Lynch, 1973), and P. w-nigrum (Boettger, 1892) were set as outgroups.…”
Section: Dna Extraction Amplification and Sequencingmentioning
confidence: 99%
“…Expeditions to remote places in the eastern slopes of the Peruvian Andes have shown that unexplored neotropical mountains are sources of unknown and endemic herpetofauna (Duellman et al 2014;Catenazzi et al 2015;Echevarría et al 2015;Chávez and Catenazzi 2016;Chávez et al 2017;Lehr and Moravec 2017;Lehr and von May 2017;Lehr et al 2017aLehr et al , 2017b. Frogs are one the most diverse herpetofaunal orders, particularly in Andean ecosystems where endemism is high (Swenson et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Frogs are one the most diverse herpetofaunal orders, particularly in Andean ecosystems where endemism is high (Swenson et al 2012). Furthermore, many of the discoveries of new amphibians are frogs (Duellman et al 2014;Catenazzi et al 2015;Chávez and Catenazzi 2016;Lehr and Moravec 2017;Lehr and von May 2017;Lehr et al 2017aLehr et al , 2017b. Among recently named frogs, most of the new Peruvian Andean species belong to the genus Pristimantis Jiménez de la Espada, 1870, which is the most diverse clade in the Neotropics (Padial et al 2014).…”
Section: Introductionmentioning
confidence: 99%